Distraction Osteogenesis Maxillary Expansion (DOME) for adult obstructive sleep apnea patients with narrow maxilla and nasal floor - Yoon, Audrey; Guilleminault, Christian; Zaghi, Soroush; Liu, Stanley Yung-Chuan (Sleep medicine, 2020)
This study correlates objective and subjective measurements associated with obstructive sleep apnea (OSA) to define the efficacy of Distraction Osteogenesis Maxillary Expansion (DOME) to treat adult OSA patients with narrow maxilla and nasal floor. This is a retrospective study reviewing cases from September 2014 through April 2018 with 75 eligible subjects. Inclusion criteria required OSA confirmed by attended polysomnography (PSG). Pre- and Post-operative clinical data were measured at the Stanford Sleep Medicine and Stanford Sleep Surgery Clinics. DOME is a two-step process starting with insertion of custom-fabricated maxillary expanders anchored to the hard palate by mini-implants followed by minimally invasive osteotomies. After maxillary expansion was complete, orthodontic treatment to restore normal occlusion was initiated. Perioperative Apnea-Hypopnea Index (AHI), Epworth Sleepiness Scale (ESS), Nasal Obstruction Symptom Evaluation (NOSE), and Oxygen Desaturation Index (ODI) were measured for 43, 72, 72, and 34 subjects respectively. Statistical analysis was performed using paired T-test with significance set at p-value < 0.05. The mean age of test subjects was 30.5 ± 8.5 years with a gender distribution of 57 males and 18 females. There was a significant reduction in pre and post-operative NOSE score (10.94 ± 5.51 to 3.28 ± 2.89, p < 0.0001), mean ESS score (10.48 ± 5.4 to 6.69 ± 4.75, p < 0.0001), and AHI (17.65 ± 19.30 to 8.17 ± 8.47, p < 0.0001) with an increased percentage of REM sleep (14.4 ± 8.3% to 22.7 ± 6.6%, p = 0.0014). No significant adverse effects were identified. DOME treatment reduced the severity of OSA, refractory nasal obstruction, daytime somnolence, and increased the percentage of REM sleep in this selected cohort of adults OSA patients with narrow maxilla and nasal floor. •Distraction Osteogenesis Maxillary Expansion (DOME) is a targeted anatomic intervention for adults with obstructive sleep apnea (OSA) presenting with narrow maxilla and nasal floor.•DOME significantly alleviates nasal obstruction.•DOME improves OSA.